Characterization of the expression pattern of the Not1 regulator of gene expression in the malaria parasite plasmodium falciparum - Tan, Aik Choong (2016)
Malaria is one of the most worrying infectious diseases worldwide. Recent discovery of the artemisinin-resistant Plasmodium species has sparked a great health concern. Studies on stress-induced defense mechanism in these parasites may provide clue on how they survive in multiple host induced stresses. The aim of the research is to investigate the alteration in protein and mRNA level of Not1.1, a component of Ccr4-Not complex, when the parasite is subjected to heat and drug-induced stress. Immunofluorescence Assay (IFA) carried out with FLAG mAb (monoclonal antibody) shows signal in the F-T996; however we also observe a weaker signal in the parent WT strain. This makes the current result inconclusive. We were unable to detect the FLAG-Not1.1 protein in the western blot analysis using FLAG mAb. Generation of monoclonal antibody against Not1.1 may help us address these issues. The existing RT-PCR data is insufficient to conclude the change in mRNA levels. The data in RT-PCR should be validated by including biological replicates and the gene expression analysis should take into account the changes in the expression profile of the Not1.1 across the life cycle under normal condition. By gaining better knowledge on how this organism responds to stressful condition, we might be able to decipher the drug resistance mechanism and develop better Malaria treatment in the future.